1980
DOI: 10.1210/endo-107-1-155
|View full text |Cite
|
Sign up to set email alerts
|

Time-Trend Analysis of Plasma Cortisol Concentrations in the Fetal Sheep in Relation to Parturition*

Abstract: Using a cortisol RIA carefully validated for specificity in fetal ovine plasma, we studied plasma cortisol time-trend changes in eight chronically catheterized sheep fetuses in the last 22 days of gestation before the spontaneous onset of labor. Best fit exponential type curves were drawn for each individual fetus to define the time before the onset of labor at which fetal plasma cortisol was rising at different rates. Fetal plasma cortisol increased at a rate of 0.5 ng ml-1 day-1 as early as 17.1 days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
73
0
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(83 citation statements)
references
References 13 publications
8
73
0
2
Order By: Relevance
“…Previous studies have reported an increase in plasma cortisol levels in fetal lambs in late gestation, beginning about 9 d before delivery (34,35). In the current study, this corresponds to infusion d 5 and 4 in control and FX-exposed fetuses, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies have reported an increase in plasma cortisol levels in fetal lambs in late gestation, beginning about 9 d before delivery (34,35). In the current study, this corresponds to infusion d 5 and 4 in control and FX-exposed fetuses, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…Our finding that maternal DM treatment at 105 dGA significantly reduced fetal cortisol and ACTH levels differs from previous studies in which fetal DM infusion had little effect on basal plasma ACTH and cortisol concentrations in fetuses Ͼ120 dGA (22,31,46). These findings are in keeping with the concept that the sensitivity of the hypothalamic-pituitary-adrenal system to negative feedback is greater earlier in gestation and disappears, thereby allowing the endogenous rise in cortisol that usually occurs at~125 dGA (6,47). We also found that maternal DM treatment reduced maternal cortisol and ACTH levels.…”
Section: Discussionsupporting
confidence: 56%
“…Administration of synthetic glucocorticoids, such as betamethasone and dexamethasone (DM), to accelerate fetal lung maturation has become a routine treatment for women who are at risk of preterm labor (1,2). This treatment is designed to elevate fetal plasma glucocorticoid levels, mimicking the maturational effects that normally occur close to term in humans and other species produced by the endogenous prepartum increases in fetal plasma cortisol (3)(4)(5)(6). Prophylactic antenatal glucocorticoid treatment has resulted in a significant decrease in preterm infant morbidity and mortality (1,(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that in the ovine fetus, plasma levels of corticosteroids are very low between 60 and 130 days of gestation, then increase dramatically during the two weeks preceding parturition (Alexander et al, 1968 ;Bassett and Thorburn, 1969 ;Magyar et al, 1980;Wintour et al, 1975). This increase results from an enhanced activity of the fetal adrenal cortex (Nathanielsz et al, 1972 ;Wintouret a/., 1975) and induces both fetal maturation (review by Liggins, 1976) and parturition (reviews by Nathanielsz, 1978; Thorburn and Challis, 1979).…”
Section: Introductionmentioning
confidence: 99%